Reemergence of yellow fever: detection of transmission in the State of São Paulo, Brazil, 2008 Reemergência de febre amarela: detecção de transmissão no Estado de São Paulo, Brasil, 2008 - Eduardo Stramandinoli Moreno; Iray Maria Rocco; Eduardo Sterlino Bergo; Roosecelis Araujo Brasil; Melissa Mascheratti Siciliano; Akemi Suzuki; Vivian Regina Silveira; Ivani Bisordi; Renato Pereira de Souza (Sociedade Brasileira de Medicina Tropical (SBMT), 2011)
INTRODUCTION: Following yellow fever virus (YFV) isolation in monkeys from the São José do Rio Preto region and two fatal human autochthonous cases from the Ribeirão Preto region, State of São Paulo, Brazil, two expeditions for entomological research and eco-epidemiological evaluation were conducted. METHODS: A total of 577 samples from humans, 108 from monkeys and 3,049 mosquitoes were analyzed by one or more methods: virus isolation, ELISA-IgM, RT-PCR, histopathology and immunohistochemical. RESULTS: Of the 577 human samples, 531 were tested by ELISA-IgM, with 3 positives, and 235 were inoculated into mice and 199 in cell culture, resulting in one virus isolation. One sample was positive by histopathology and immunohistochemical. Using RT-PCR, 25 samples were processed with 4 positive reactions. A total of 108 specimens of monkeys were examined, 108 were inoculated into mice and 45 in cell culture. Four virus strains were isolated from Alouattacaraya. A total of 931 mosquitoes were captured in Sao Jose do Rio Preto and 2,118 in Ribeirão Preto and separated into batches. A single isolation of YFV was derived from a batch of 9 mosquitoes Psorophoraferox, collected in Urupês, Ribeirão Preto region. A serological survey was conducted with 128 samples from the municipalities of São Carlos, Rincão and Ribeirão Preto and 10 samples from contacts of patients from Ribeirão Preto. All samples were negative by ELISA-IgM for YFV. CONCLUSIONS: The results confirm the circulation of yellow fever, even though sporadic, in the Sao Paulo State and reinforce the importance of vaccination against yellow fever in areas considered at risk. INTRODUÇÃO: A partir do isolamento do vírus febre amarela (VFA), de macacos, da região de São José do Rio Preto e de dois casos humanos autóctones fatais, da região de Ribeirão Preto, Estado de São Paulo, foram realizadas duas expedições para pesquisa entomológica e avaliação ecoepidemiológica. MÉTODOS: Um total de 577 amostras de humanos, 108 de macacos e 3.049 mosquitos foram analisados por um ...